Endosperm Tolerance of Paternal Aneuploidy Allows Radiation Hybrid Mapping of the Wheat D-Genome and a Measure of γ Ray-Induced Chromosome Breaks - Tiwari, Vijay K.; Riera-Lizarazu, Oscar; Gunn, Hilary L.; Lopez, KaSandra; Iqbal, M. Javed; Kianian, Shahryar F.; Leonard, Jeffrey M. (PLOS ONE, 2012)
Physical mapping and genome sequencing are underway for the ≈17 Gb wheat genome. Physical mapping methods independent of meiotic recombination, such as radiation hybrid (RH) mapping, will aid precise anchoring of BAC contigs in the large regions of suppressed recombination in Triticeae genomes. Reports of endosperm development following pollination with irradiated pollen at dosages that cause embryo abortion prompted us to investigate endosperm as a potential source of RH mapping germplasm. Here, we report a novel approach to construct RH based physical maps of all seven D-genome chromosomes of the hexaploid wheat ‘Chinese Spring’, simultaneously. An 81-member subset of endosperm samples derived from 20-Gy irradiated pollen was genotyped for deletions, and 737 markers were mapped on seven D-genome chromosomes. Analysis of well-defined regions of six chromosomes suggested a map resolution of ∼830 kb could be achieved; this estimate was validated with assays of markers from a sequenced contig. We estimate that the panel contains ∼6,000 deletion bins for D-genome chromosomes and will require ∼18,000 markers for high resolution mapping. Map-based deletion estimates revealed a majority of 1–20 Mb interstitial deletions suggesting mutagenic repair of double-strand breaks in pollen provides a useful resource for RH mapping and map based cloning studies.